Causas para el bajo rendimiento en primero y segundo nivel de la carrera de Educación Básica, (periodos 49 y 50) de la Universidad Politécnica Salesiana– sede Quito - Aguilar Andrade, Anthony Alberto (2018)
This case study will be about the causes for low academic performance within the First and Second levels of the Career of Basic Education, during the 49th and 50th periods at the Salesian Polytechnic University in the Quito Campus. In order to identify and expose the reasons or factors by which a university student may have a low academic performance. In order to carry out this research, the following question was taken as a starting point: What are the causes for the students of the Career of Basic Education, Quito Campus, to have low academic performance? This led to a bibliographical research, with the aim of finding the theoretical foundation for the causes of low performance. Then we proceeded to the field work, in where several interviews were conducted and valuable information was obtained which was later contrasted with the bibliographic information. Thanks to the analysis of the data, it was determined that the factors that affect low performance range are: personal, family and academic ones, which are decisive when distinguishing between high performance and low performance. This is how this case analysis presents the causes or factors that influence the academic life of a university student for low performance to become present.